2013
DOI: 10.1073/pnas.1303708110
|View full text |Cite
|
Sign up to set email alerts
|

Family of pH (low) insertion peptides for tumor targeting

Abstract: Cancer is a complex disease with a range of genetic and biochemical markers within and among tumors, but a general tumor characteristic is extracellular acidity, which is associated with tumor growth and development. Acidosis could be a universal marker for cancer imaging and the delivery of therapeutic molecules, but its promise as a cancer biomarker has not been fully realized in the clinic. We have discovered a unique approach for the targeting of acidic tissue using the pH-sensitive folding and transmembra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
275
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(295 citation statements)
references
References 20 publications
17
275
1
Order By: Relevance
“…The delivery approach we propose is based on the energy of membrane-associated folding of peptides from the pHLIP family to target cellular membranes in a pHdependent manner (22,24,37). At pH < 7.0, pHLIPs insert into the lipid bilayer of the membrane, which is accompanied by a coil-helix transition and formation of a transmembrane helix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The delivery approach we propose is based on the energy of membrane-associated folding of peptides from the pHLIP family to target cellular membranes in a pHdependent manner (22,24,37). At pH < 7.0, pHLIPs insert into the lipid bilayer of the membrane, which is accompanied by a coil-helix transition and formation of a transmembrane helix.…”
Section: Discussionmentioning
confidence: 99%
“…The pH-sensitive targeting agents we are developing are based on the action of a family of pHLIPs (pH Low-Insertion Peptides), which can "sense" acidity at the surface of cancer cells and deliver diagnostic and therapeutic molecules to tumors of different origins (20)(21)(22)(23)(24)(25). It was shown that pHLIP can promote fusion of liposomes with cancer cells and cellular delivery of various payloads (26,27), including small gold nanoparticles (26).…”
mentioning
confidence: 99%
“…Thus, acidity may provide a universal biomarker for tumor targeting that is not subject to the selection of resistant cell lines (10). pH low insertion peptides (pHLIPs) are a class of membrane-binding peptides that specifically target acidic cells in vitro and in vivo (11) by inserting across cellular membranes when the extracellular pH is low (12). pHLIPs conjugated with fluorescent dyes have been used to differentiate normal from neoplastic tissue in various animal tumor models (12)(13)(14)(15) and in human biopsy head and neck samples (16,17).…”
mentioning
confidence: 99%
“…pH low insertion peptides (pHLIPs) are a class of membrane-binding peptides that specifically target acidic cells in vitro and in vivo (11) by inserting across cellular membranes when the extracellular pH is low (12). pHLIPs conjugated with fluorescent dyes have been used to differentiate normal from neoplastic tissue in various animal tumor models (12)(13)(14)(15) and in human biopsy head and neck samples (16,17). This report uses an indocyanine green (ICG) pHLIP conjugate for the diagnosis of urothelial carcinoma and precancerous lesions in fresh human radical cystectomy samples ex vivo and points the way toward a wide range of diagnostic and therapeutic alternatives.…”
mentioning
confidence: 99%
“…To exploit the acidic extracellular pH as a targeting strategy for our polypyrrole nanocontrasting agent, we utilized a V7 pHLIP (pH Low Insertion Peptide), which changes conformation in response to its environment. In neutral pHe (7.2-7.4), it maintains a globular form and transforms to a transmembrane alpha-helix at acidic pHe conditions (6.4-6.8), this then allows the conjugated particle to insert and anchor into tumor cells [31][32][33].…”
Section: Chuongmentioning
confidence: 99%